A Retrospective Study on Proficiency Testing Samples in the Field of Laboratory Animal Testing from 2013 to 2022 - QIAO Han; WEI Jie; WANG Feifei; WANG Hong; XING Jin; FU Rui; XIAO Jing; ZHAO Meng; YUE Bingfei; XIANG Xinhua (Shiyan dongwu yu bijiao yixue, 2022)
Objective To analyze the status of proficiency testing samples in the field of laboratory animal testing, and to evaluate the role of the testing samples in the laboratory animal laboratory proficiency testing program.MethodsA retrospective study was conducted to compare the 30 proficiency testing plans and reports in the field of laboratory animal organized by National Institute for Food and Drug Control (NIFDC) from 2013 to 2022. The type, quantity, preparation method, homogeneity and stability of the proficiency testing samples, as well as the satisfaction of the participating units to the samples were analyzed. Then, the supply of new samples, the addition of quantitative projects, the improvement of stability research and the attention to customer needs were discussed.ResultsThe 30 proficiency testing programs included 10 items in the direction of bacteria, 10 items in the direction of virus and 10 items in the direction of genetics in the field of experimental animals. A total of 80 non-nucleic acid samples (including serums, feces, tracheal flushing fluid and proteins) and 4 nucleic acid samples were provided, all of which were qualitative samples. Compared with nucleic acid samples, non-nucleic acid samples always required large numbers of animals for sample preparation. The pass rate of homogeneity verification of the sample was 100%, but there is no quantitative study at present. Stability verification can be conducted for the short-term storage, transportation, freeze-thaw, different concentrations and terminal stability of different samples, but it lacks long-term stability verification.ConclusionIn the past ten years, the proficiency testing samples have basically met the basic requirements of the proficiency testing plan of laboratory animal testing area. However, the provision of nucleic acid samples should be reasonably increased; quantitative research samples and projects should be added; the influence of proficiency testing in the field of laboratory animal testing should be continuously expanded and maintain high-quality services.